An Experimental and Computational Study of β-AgVO3: Optical Properties and Formation of Ag Nanoparticles - De Oliveira, Regiane Cristina; Assis, Marcelo; Teixeira, Mayara Mondego; Da Silva, Maya Dayana Penha; Li, Máximo Siu; Andres, Juan; Gracia, Lourdes; Longo, Elson [UNESP] (American Chemical Society (ACS), 2016)
This article aims to gather together in one place and for first time the formation process of Ag nanoparticles (NPs) on β-AgVO3 crystals, driven by an accelerated electron beam from an electronic microscope under high vacuum. Synthesis and optical properties of β-AgVO3 are reported, and the relationship between structural disorder and photoluminescence emissions is discussed. First principle calculations, within a QTAIM framework, have been carried out to provide a deeper insight and understanding of the observed nucleation and early evolution of Ag nanoparticles (NPs) on β-AgVO3 crystals. The Ag nucleation and formation is a result of structural and electronic changes of the [AgO5] and [AgO6] clusters, consistent with Ag metallic formation.